Effect of Cu Ion Concentration on Microstructures and Mechanical Properties of Nanotwinned Cu Foils Fabricated by Rotary Electroplating - Yu-Wen Hung; Dinh-Phuc Tran; Chih Chen (Nanomaterials, 2021)
Rotary electroplating was employed to fabricate high-strength nanotwinned copper (nt-Cu) foils serving as a current collector for high energy-density lithium ion batteries (LIBs). The effect of Cu ion concentration on the microstructural and mechanical properties of the nt-Cu foils was then investigated. Formation of nano-scaled grains was found at the bottom. Its size gradually increases toward the top surface to form a microstructural mixture of gradient nano-scaled and columnar grains in the upper region. Experimental results show that the grains and elongation of the nt-Cu foils increase with increasing concentration of Cu ions. However, a trade-off between tensile strength and elongation is present. The elongation of nt-Cu foils has been enhanced by 22% (from 3.1% to 3.8%) while 8.3% and 3.9% reductions in ultimate tensile strength (UTS) and yield stress (YS) are seen. The current study shows a promising method to tune and optimize the microstructure and mechanical properties of such nt-Cu foils for various applications.